Hypoglossal Schwannoma Masquerading as a Carotid Body Tumor - Matthew K. Lee; Douglas R. Sidell; Abie H. Mendelsohn; Keith E. Blackwell (Case Reports in Otolaryngology)
Study Objective. To describe the clinical presentation, evaluation, and treatment of a hypoglossal schwannoma. Methods. We report an unusual case of a hypoglossal schwannoma presenting as a pulsatile level II neck mass at the bifurcation of the external and internal carotid arteries, mimicking a carotid body tumor. Radiologic findings are reviewed in detail. Results. A 59-year-old female presented to a tertiary care medical center with complaints of a pulsatile right-sided neck mass. An MRA of the neck was obtained demonstrating a 5 cm mass located at the carotid artery bifurcation and causing splaying of the internal and external carotids. Based on clinical presentation and imaging, a diagnosis of a carotid body tumor was conferred and the patient scheduled for excision. Intraoperatively, the mass was noted to arise from the hypoglossal nerve, remaining independent of the carotid artery. On histopathologic analysis, the mass was determined to be consistent with hypoglossal schwannoma. Conclusion. Though rare, the hypoglossal schwannoma should remain a consideration in the evaluation of a parapharyngeal space mass. As this report demonstrates, the clinical and radiologic presentation of a hypoglossal schwannoma may closely mimic that of the more common carotid body tumor.